Immunogenic and Protective Features of the Recombinant Vaccinia Virus Strain Expressing Cassette of Genes of Marburg Virus Structural Proteins - A. V. Semenova; G. F. Sivolobova; A. A. Grazhdantseva; S. A. P’yankov; I. S. Shul’gina; O. S. Taranov; O. V. P’yankov; D. V. Antonets; L. I. Karpenko; E. V. Starostina; M. V. Borgoyakova; A. N. Chikaev; et al. (Проблемы особо опасных инфекций, 2022)
The aim of the study was to create a highly immunogenic vaccine construct based on a recombinant variant of a replication-defective MVA strain of vaccinia virus, expressing virus-like particles that mimic natural infection with Marburg virus. Materials and methods. The recombinant virus was obtained through recombination between homologous viral DNA sequences and the insertion plasmid pDel2-GP-VP-Pat which carries transgenes of the structural proteins GP and VP40 of Marburg virus, flanked by fragments of MVA strain genome. Structure of the recombinant virus was confirmed in PCR and using sequencing, transgenes expression was analyzed by Western blotting, viruslike particles formation was recorded using electron microscopy. Evaluation of immunogenicity and protectivity was carried out using a guinea pig model. The antibody titer was determined in enzyme-linked immunosorbent assay. To assess T-cell response, the intracellular staining of cytokines was used, followed by analysis of samples on a flow cytometer. Results and discussion. On the basis of highly attenuated MVA strain of vaccinia virus a recombinant variant MVA-GP-VP40-MARV has been constructed, carrying a cassette of transgenes, GP and VP40, of Marburg virus in the region of deletion II of the genome. The expression of transgenes in MVA-permissive CER cells infected with recombinant MVA-GP-VP40-MARV strain and secretion of GP and VP40 proteins into culture medium have been demonstrated. Electron microscopy analysis has revealed the presence of Marburg virus-like particles in the culture medium of cells 12 hours after infection. Double vaccination of guinea pigs with MVA-GP-VP40-MARV strain at a dose of 108 PFU/animal induced the formation of antibodies to Marburg and vaccinia viruses, as well as 100 % protection against lethal Marburg virus infection (50 LD50). Using original TEpredict software, the structure of T-helper epitopes of GP protein has been predicted. Using the ICS method, the biological activity of these epitopes has been experimentally confirmed and it was shown that they provide the induction of a T-cell immune response as part of the MVA-GP-VP40-MARV vaccine construct.